Digestibilidade aparente do hidrolisado proteico de resíduos de filetagem de tilápia e sua inclusão em rações para pós larvas de tilápia do Nilo - Farias, Antônio Carlos do Amaral (2019)
The objective of this work was to determine the apparent digestibility coefficients (CDA) of filletting protein hydrolyzate (HPRT) by Nile tilapia and to evaluate zootechnical performance and stress responses to the management of post - larvae of this species fed diets containing HPRT. For the conduction of the digestibility test, 120 juveniles of tilapia with a mean weight of 150 g were randomly distributed in 12 conical cylindrical tanks, suitable for fecal collection. The experiment consisted of two treatments and six replicates. Two experimental diets, one reference and another test diet, containing 80% of the reference diet and 20% of the food under study were elaborated. For the performance experiment with post larvae, 1250 animals with a mean weight of 0.01g were distributed in 25 boxes of polyethylene with a useful volume of 70 liters. Diets with inclusion levels of 0, 2.5; 5.0; 7.5 and 10% of HPRT, totaling five treatments and five replicates. The fish were fed at 8h, 10: 30h, 13: 30h, 15: 30h and 17: 30h for 30 days. After the experimental period the fish were weighed and measured to evaluate the zootechnical parameters and returned to their experimental units, where they remained for three more days receiving the same diets and then were submitted to stress by management simulation for seven minutes. Mortality was recorded for 24 hours. The data were submitted to analysis of variance, in case of a significant effect (P <0.05) the Tukey multiple comparison test was performed, at 5% of significance. The values obtained for the CDA of energy and crude protein were 84.59 and 91.89%, respectively, with digestible energy of 4444.36 kcal / kg and digestible protein of 60.26%. The highest mean weight (grams) and length (centimeters) between HPRT inclusion levels were observed in animals receiving the feed with inclusion of 5%, with 4.95 ± 0.26 g and 5.5 ± 0, 26 cm, but did not differ statistically from the fish that received the diet with 0% (P> 0.05) that presented weight of 4.74 ± 0.21 g and length of 5.29 ± 0.12 cm. In the test of resistance to air stress, the control treatment, without the inclusion of hydrolyzate, presented higher mortality (P <0.05) (8.40%). It was concluded that the inclusion of 5% of HPRT in rations for post-larvae of tilapia, replacing fish meal, improves performance and that the inclusion of this ingredient improved fish resistance to stress from exposure to air.